Nanoemulsions and acidified milk gels as a strategy for improving stability and antioxidant activity of yarrow phenolic compounds after gastrointestinal digestion. (April 2020) - Villalva, M.; Jaime, L.; Arranz, E.; Zhao, Z.; Corredig, M.; Reglero, G.; Santoyo, S.
Graphical abstract: Highlights: Casein-based delivery systems improved yarrow phenolic compounds stability. Nanoemulsions partially protected yarrow phenolic compounds during digestion. Yarrow phenolics included in acidified milk gels were protected during digestion. After digestion, phenolics in milk gels showed the highest antioxidant activity. Milk gels could be used to develop dairy products enriched with phenolic compounds. Abstract: The aim of this study was to improve the stability and antioxidant activity of yarrow phenolic compounds upon an in vitro simulated gastrointestinal digestion. Therefore, two types of caseins-based delivery systems, sodium caseinate stabilized nanoemulsions (NEs) and glucono delta-lactone acidified milk gels (MGs), were formulated containing an ultrasound-assisted yarrow extract (YE) at two concentrations (1 and 2.5 mg/mL). Formulations with 1 mg/mL of YE were chosen based on their higher encapsulation efficiency to perform the in vitro digestion experiments. After digestion, YE-loaded NEs only partially protected phenolic compounds from degradation; meanwhile the phenolic composition of YE including in MGs after digestion was quite similar to undigested YE. Moreover, the antioxidant activity of MGs after digestion was higher than NEs digested samples, which confirms the higher protection of YE phenolic compound by the milk gels systems. This research demonstrated the potential use of acidified MGs as carriers to improve the stability and antioxidant activity of yarrow phenolic compounds. Therefore, these matrices could be employed to develop new dairy products enriched with phenolic compounds.